A Chromosomal Deletion and New Frameshift Mutation Cause ARSACS in an African-American - Dougherty, Sean C.; Harper, Amy; Al Saif, Hind; Vorona, Gregory; Haines, Scott R. (Frontiers in Neurology, 2018)
Autosomal Recessive Spastic Ataxia of Charlevoix-Saguenay (ARSACS) is a rare, progressive, neurodegenerative disease characterized by ataxia, spasticity and polyneuropathy. First described in the French-Canadian population of Quebec in 1978, ARSACS has since been identified in multiple patients worldwide. In this clinical case report, we describe the evaluation of an 11-year-old African-American male who presented to neuromuscular clinic for assessment of a gait abnormality. He had a history of gross motor delay since early childhood, frequent falls and a below average IQ. Chromosomal microarray revealed a 1.422 megabase loss in the 13q12.12 region, which includes the SACS gene. Next Generation Sequencing then showed a novel, predicted to be pathogenic missense mutation (c.11824dup) of this gene. His clinical presentation and neurological imaging further confirmed the diagnosis of ARSACS. To our knowledge, this is the first reported case of this disease in the African-American population of the United States. This case report further highlights the growing trend of identifying genetic diseases previously restricted to single, ethnically isolated regions in many different ethnic groups worldwide.